Participatory Methods and UCA Project: understanding technologies as culture - Magda Pischetola; Lyana Thediga Miranda (Universidade Federal de Santa Catarina, 2015)
Abstract In the complex and changing context of digital culture, the media become an important space of relation, as they have the crucial role of articulating new cultural logics that lead to disruptions in the school environment. To understand this change, new methods of analysis and research have been created, the so-called Participatory Methodologies. They are action research strategies aimed at intervening in a given social situation. In the analysis proposed here, such methodologies will help us to address the challenge of involving digital technologies in school culture, through the participation of different individuals involved. Two qualitative case studies about the project Um Computador por Aluno - the Brazilian One Laptop per Child -, carried out in 2012 in the schools of Santa Catarina and Bahia, are the first of two phases of the research presented. The results concern a "vertical" form of technology insertion in schools, which led to frustration and de-motivation at several levels. Starting from these considerations, the second stage of research proposes a pedagogical intervention in one of four schools in the field. The methodologies of participatory video and photography are chosen as possibilities of action-reflection-action on the sociocultural reality of students through the experience of sharing. The results show the importance of carrying out creative activities, appropriate to a social conception of learning, as well as the centrality of children and youth as agency and a broader need to redefine the relationship between teacher and student, in a more "horizontal" perspective process of teaching and learning. Keywords: Projeto UCA. Participatory Research Method. Innovative teaching-learning.